COMPARATIVE RESEARCHES IN UZBEK LITERATURE (OYBEK AND THE WORLD LITERATURE) - Gulnoz Iskandarovna Khallieva (Scholar Express Journal, 2025)
As a result of scientific and literary contacts, real works quickly penetrate into the literary world of other nations and, to some extent, become their spiritual property. This means that the works of Navoi, Babur, Shakespeare, Dante and many other poets and writers will become the common intellectual property of the peoples of the world. In this process, comparative research plays a special role. As a result of scientific and literary contacts, real works quickly penetrate into the literary world of other nations and, to some extent, become their spiritual property. This means that the works of Navoi, Babur, Shakespeare, Dante and many other poets and writers will become the common intellectual property of the peoples of the world. In this process, comparative research plays a special role.
Keywords: Comparative researches; Uzbek literature; world literature